The Effect of Scramble to Improving Vocabulary Mastery of the First Year Student at State Vocational High School 1 Pematangsiantar - Mega Silvia Sitompul; Indah Manik (Journal on Education, 2023)
In a community, communication is the means by which ideas and messages are passed from one person to another. Language is necessary for individuals to communicate. One of the tools of communication is language. Language is a tool for interaction or communication in society, providing people with ideas, food for thought, and specialized information. Language is either arbitrary or the primary means of inter-human communcation. Language is a system that links gestures and sounds to meaning. The purpose of this study, which was to determine whether using the scramble game improved students' vocabulary in any different meaningful ways and to determine the motivational factors between the participants, was to examine how scramble might be used to improve students' vocabulary ability in the classroom.